The Changes in the Frog Gut Microbiome and Its Putative Oxygen-Related Phenotypes Accompanying the Development of Gastrointestinal Complexity and Dietary Shift - Zhang, Mengjie; Chen, Hua; Liu, Lusha; Xu, Liangliang; Wang, Xungang; Chang, Liming; Chang, Qing; Lu, Guoqing; Jiang, Jianping; Zhu, Lifeng (Frontiers in Microbiology, 2020)
There are many examples of symbiotic and reciprocal relationships in ecological systems; animal gut microbiome-host interactions are one such kind of bidirectional and complex relationship. Here, we utilized several approaches (16S rRNA gene sequencing, metagenomics, and transcriptomics) to explore potential gut microbiome-host interactions accompanying the development of gastrointestinal complexity and dietary shift from metamorphosis to maturity in ornamented pygmy frogs (Microhyla fissipes). We identified possible coevolution between a particular gut microbial group (increased putative fat-digesting Erysipelotrichaceae and chitin-digesting Bacteroides and Ruminococcaceae) with the host dietary shift (from herbivore to insectivore (high proportion of dietary chitin and fat)) during metamorphosis. We also found that the remodeling and complexity of the gastrointestinal system during metamorphosis might have a profound effect on the gut microbial community (decreasing facultative anaerobic Proteobacteria and increasing anaerobic Firmicutes) and its putative oxygen-related phenotypes. Moreover, a high proportion of chitin-digesting bacteria and increased carbohydrate metabolism by gut microbiomes at the climax of metamorphosis would help the frog’s nutrition and energy needs during metamorphosis and development. Considering the increased expression of particular host genes (e.g., chitinase) in juvenile frogs, we speculate that host play an important role in amphibian metamorphosis, and their symbiotic gut microbiome may help in this process by providing the nutrition and energy needs . Here we provide this basic information for the amphibian conservation and managements.